Total Physical Response with Communicative Approach (TPRCA) Method in Primary School English Learning - Purwono, Prahoro Yudo (Jurnal Pendidikan Bahasa Inggris undiksha, 2023)
English as an International language is a necessity in this era. However, in its implementation in elementary school, it was very difficult to teach English to children. Thus, an innovation was needed. One of them was learning English integrated with Indonesian culture. However, on the other hand, there were competencies that must be achieved by students in elementary school, namely oral skills, while the existing methods focus more on vocabulary and grammar. Therefore, the Total Physical Response with Communicative Approach (TPRCA) method based on the introduction of Indonesian culture was proposed. The purpose of this research was to develop the TPRCA method based on the introduction of Indonesian culture for students in elementary schools and how it is implemented. The research method used was ADDIE with a literature study approach. Data was collected through literature study, then analyzed using qualitative methods such as reduction and results analysis. There are 5 methods such as giving orders, role playing, dialogue, storytelling, reading and writing. The competencies to be achieved were communicative, able to understand the text, able to write a simple summary, able to mention things related to Indonesian culture in English, and able to give reciprocity to the commands given in English. The conclusion was that the development stage starts from analysis, competency adjustment, formulation of skills and indicators, validity testing, to the application and evaluation stages. The application started from the teacher explaining the method used, the implementation of learning, till the test stage.